Paediatrician and Caregiver Awareness of Cryptosporidiosis and Giardiasis in Children: US Survey Responses. (18th December 2015) - Munoz, F. M.; Attias, E.; Czinn, S. J.; Black, J.
Summary: There appears to be no published information concerning the awareness and knowledge about diarrhoea caused by Cryptosporidium spp. or Giardia lamblia among US paediatricians and caregivers of young children. Two concurrent, separate surveys were conducted among paediatricians and caregivers (~1000 respondents in each survey) of children ages 1–12 years concerning their knowledge, perceptions and attitudes in the diagnosis and treatment of parasitic diarrhoea. Awareness of parasite‐induced diarrhoea was low for specific aspects among both paediatricians and caregivers. Educational efforts to improve awareness on the appropriate clinical presentation, management and treatment of cryptosporidiosis and giardiasis in children with persistent diarrhoea should be undertaken.